2022
DOI: 10.14254/2071-8330.2022/15-2/15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of fiscal policy shocks in the Baltic region

Abstract: The study aims to compare the effects of fiscal policy shocks in three Baltic countries – Estonia, Latvia, and Lithuania - within SVAR framework, using the identification scheme proposed by Blanchard and Perotti (2002). The time sample covers quarterly data over the period of 2002q1-2019q4. The main idea of the study is to identify the effects of fiscal policy shocks in three euro area member states under a single monetary policy of the European Central Bank, but with country-specific fiscal policy shaped by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Based on the above calculations, we can fully confirm hypothesis H1. As in the works of other researchers, e.g., Szymańska (2022), it was found that EU countries are very heterogeneous in terms of development trends and the influence of social content factors. There are two groups of countries: with a positive impact of social expenditures on economic development, as well as countries where negative dependencies are already observed, which may be a sign of the effect of declining efficiency as a result of the previously achieved very high level of social protection of the population due to the financing of national social programs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Based on the above calculations, we can fully confirm hypothesis H1. As in the works of other researchers, e.g., Szymańska (2022), it was found that EU countries are very heterogeneous in terms of development trends and the influence of social content factors. There are two groups of countries: with a positive impact of social expenditures on economic development, as well as countries where negative dependencies are already observed, which may be a sign of the effect of declining efficiency as a result of the previously achieved very high level of social protection of the population due to the financing of national social programs.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, some authors have confirmed the positive role of social spending in economic processes, in particular in GDP growth, at least due to education and health spending (Stuckler et al, 2017;Kutasi & Marton, 2020), although the total amount of government expenditure has a positive effect on GDP growth (Ahuja & Pandit, 2020). At the same time, the results were obtained indicating the absence of such a visible connection (Cammeraat, 2020), its different orientation even in relatively close countries (Szymańska, 2022), or a positive effect on real GDP in the medium term but a negative effect in the long run (Kim & Ahn, 2020).…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, researchers find that in both developed http://dx.doi.org/10.21511/bbs.19 (1).2024.07 and developing countries, higher CBI levels are associated with reduced volatility in inflation. Even after considering additional variables such as fiscal policy, external shocks, and the degree of economic development that might impact inflation stability, this relationship persists (Szymańska, 2022). Additionally, the study offers evidence that suggests a stronger correlation between CBI and inflation stability may exist in countries with higher levels of instability and corruption.…”
Section: Literature Reviewmentioning
confidence: 79%
“…The consequences of migration attract no less attention in view of both the negatives and potential benefits associated with migratory changes in the composition of communities. Among the typical areas of such research are changes in the labor market (Al-Dalahmeh & Dajnoki, 2021; Urbański, 2021), especially regarding the employment of highly educated workers (Oliinyk et al, 2022;Attamah et al, 2023), changes in earnings unfavorable for the locals (Kersan-Škabić & Blažević Burić, 2022), and the tax burden associated with changes in social policy (Szymańska, 2022). Such changes are especially noticeable for communities dependent on government financial assistance in forming their budgets (Gavkalova et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%